Dissociation energies of Ag-RG (RG = Ar, Kr, Xe) and AgO molecules from velocity map imaging studies. - Cooper, G; Kartouzian, A; Gentleman, A; Iskra, A; van Wijk, R; Mackenzie, S (AIP Publishing, 2015)
The near ultraviolet photodissociation dynamics of silver atom-rare gas dimers have been studied by velocity map imaging. Ag-RG (RG = Ar, Kr, Xe) species generated by laser ablation are excited in the region of the C ((2)Σ(+))←X ((2)Σ(+)) continuum leading to direct, near-threshold dissociation generating Ag* ((2)P3/2) + RG ((1)S0) products. Images recorded at excitation wavelengths throughout the C ((2)Σ(+))←X ((2)Σ(+)) continuum, coupled with known atomic energy levels, permit determination of the ground X ((2)Σ(+)) state dissociation energies of 85.9 ± 23.4 cm(-1) (Ag-Ar), 149.3 ± 22.4 cm(-1) (Ag-Kr), and 256.3 ± 16.0 cm(-1) (Ag-Xe). Three additional photolysis processes, each yielding Ag atom photoproducts, are observed in the same spectral region. Two of these are markedly enhanced in intensity upon seeding the molecular beam with nitrous oxide, and are assigned to photodissociation of AgO at the two-photon level. These features yield an improved ground state dissociation energy for AgO of 15 965 ± 81 cm(-1), which is in good agreement with high level calculations. The third process results in Ag atom fragments whose kinetic energy shows anomalously weak photon energy dependence and is assigned tentatively to dissociative ionization of the silver dimer Ag2.